Comparative analysis of chloroplast genome and evolutionary history of Hemerocallis - Wu, Jiang; Gao, Yang; Wang, Jinyao; Guo, Aihua; Qin, Nannan; Xing, Guoming; Li, Sen (Frontiers in Genetics, 2024)
Members of the genus Hemerocallis have significant value as ornamental, edible, and medicinal plants, particularly in China, where they have been utilized for thousands of years as both a vegetable and Traditional Chinese Medicine (TCM). Hemerocallis species exhibit strict control over flowering time, with individuals flowering either diurnally or nocturnally. However, our understanding of the evolutionary history of this genus, especially concerning important horticultural traits, remains limited. In this study, sequencing and assembly efforts were conducted on 73 samples within the Hemerocallis genus. All accessions were classified into two distinct groups based on their diurnal (daylilies) or nocturnal (nightlilies) flowering habits. Comparative analysis of the chloroplast genomes from these two groups identified fifteen variant hotspot regions, including fourteen SNPs and one deletion, which hold promise for the development of molecular markers for interspecific identification. Phylogenetic trees, generated through both maximum-likelihood (ML) and Bayesian inference (BI) methods using 76 shared protein-coding sequences, revealed that diurnal flowering evolved prior to nocturnal flowering. The divergence between the two groups is estimated to have occurred approximately 0.82 MYA (95%CI: 0.35-1.45 MYA). The ancestral state of Hemerocallis is hypothesized to have featured diurnal flowering with orange yellow petals. This study marks the first reconstruction of the evolutionary history and ancestral state of the genus Hemerocallis. The findings contribute significantly to our understanding of the adaptation and speciation history within the genus.